The optimation of cow-calf beef cattle and paddy farming integration on farmer household - Ekowati, T.; Prasetyo, E.; Handayani, M. (Diponegoro University, 2020)
Farmer households generally operate food crops and livestock subsectors that have not fully implemented well, so an optimal farming has not been achieved. This study aimed to analyze optimation of cow-calf beef cattle and paddy farming integration and simulation changing in input prices and the usage of resources to the optimal model. Survey method was used in the research in Grobogan Regency by determining Wirosari District and Purwodadi District. Quota sampling method is used to determine the number of respondents without counting the population as a sampling frame. The number of respondents in each district was 40 farmers so the total respondent was 80 farmers. Data were analyzed using linear programing. Results showed that optimum conditions of integration were achieved in 0.45 ha land, 2.75 AU of cow-calf beef cattle with maximum income of IDR 52,112,440/year. The simulation results regarding in changing in input usege indicated that the addition of 0.25% land area gives a change in scale of cow-calf beef cattle by 0.018% and income of 14.78%. In conclusion, integration optimation was achieved on 0.4 5ha land, 2.75 UT cow-calf beef cattle and optimal solution simulations indicated that farmers have the ability to develop their farming.